2014
DOI: 10.1186/1476-4598-13-91
|View full text |Cite
|
Sign up to set email alerts
|

Epidithiodiketopiperazines (ETPs) exhibit in vitro antiangiogenic and in vivo antitumor activity by disrupting the HIF-1α/p300 complex in a preclinical model of prostate cancer

Abstract: The downstream targets of hypoxia inducible factor-1 alpha (HIF-1α) play an important role in tumor progression and angiogenesis. Therefore, inhibition of HIF-mediated transcription has potential in the treatment of cancer. One attractive strategy for inhibiting HIF activity is the disruption of the HIF-1α/p300 complex, as p300 is a crucial coactivator of hypoxia-inducible transcription. Several members of the epidithiodiketopiperazine (ETP) family of natural products have been shown to disrupt the HIF-1α/p300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 35 publications
1
59
0
Order By: Relevance
“…Tumor cells must adapt to a hypoxic environment to survive and grow. This is mediated by hypoxia-inducible factor (HIF-1), whereby the O 2 -regulated HIF-1a subunit of the HIF-1 transcription factor is required for activation of multiple genes involved in tumor progression and angiogenesis [69]. Under hypoxic conditions, HIF-1a undergoes nuclear translocation where it interacts with HIF-1b and binds to target DNA sequences.…”
Section: Gliotoxin Impact On Animal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor cells must adapt to a hypoxic environment to survive and grow. This is mediated by hypoxia-inducible factor (HIF-1), whereby the O 2 -regulated HIF-1a subunit of the HIF-1 transcription factor is required for activation of multiple genes involved in tumor progression and angiogenesis [69]. Under hypoxic conditions, HIF-1a undergoes nuclear translocation where it interacts with HIF-1b and binds to target DNA sequences.…”
Section: Gliotoxin Impact On Animal Cellsmentioning
confidence: 99%
“…Indeed, Zn 2+ supplementation of ruminant diets is an effective prophylactic treatment for this disease [73]; it is tempting to speculate that this could be effected via disruption of the HIF-1a-p300 adaptive response. More recently it has been shown that gliotoxin, chaetocin, and chetomin could significantly decrease tumor growth in a prostate cancer xenograft model system [69]. Although gliotoxin exposure did not impact on the expression of HIF-1a regulated genes, these authors speculated that the antitumor activity of gliotoxin could be mediated via farnesyltransferase inhibition because inhibition of this enzyme can attenuate angiogenesis by interfering with endothelial cell migration [74].…”
Section: Gliotoxin Impact On Animal Cellsmentioning
confidence: 99%
“…Several compounds have been reported to inhibit activity of HIF-1. Kwon et al, 2012; In particular, natural products such as Chetomin, (Kung et al, 2004) and other epidithioketopiperazine (ETP)-containing small molecules (Reece et al, 2014) have been reported to be potent HIF-1α:p300 inhibitors. However, the ETP motif has been shown to chelate one of the structurally important zinc atoms in p300/CBP, so this class of molecules are unlikely to be selective inhibitors.…”
Section: -The Hif-1:p300/cbp Interactionmentioning
confidence: 99%
“…In fact, studies have effectively demonstrated inhibitors of this interaction in different cancers. 116,158,187,207 In several glioma cell lines, the inhibitor arylsulfonamide interfered with HIF-1 signaling and disrupted HIF-1a interaction with the nuclear cofactors CBP/p300, inhibiting in vivo glioma growth, 247 further suggesting the potential of the HIF-1a/CBP/p300 interaction as a therapeutic target in GBM.…”
Section: Cbp/p300mentioning
confidence: 99%